Предмет: Химия,
автор: selgameoverr
Осуществите превращения по схеме: HF → F2 → FeF3 →Fe(OH)3 → Fe2O3 →FeF3 → F2
Ответы
Автор ответа:
11
2HF ->H2+F2
2Fe+3F2=2FeF3
FeF3+3NaOH=Fe(OH)3+3NaF
2Fe(OH)3-> Fe2O3+3H2O
Fe2O3+6HF=2FeF3+3H2O
2FeF3->2Fe+3F2
2Fe+3F2=2FeF3
FeF3+3NaOH=Fe(OH)3+3NaF
2Fe(OH)3-> Fe2O3+3H2O
Fe2O3+6HF=2FeF3+3H2O
2FeF3->2Fe+3F2
Похожие вопросы
Предмет: История,
автор: egorsirotenko12
Предмет: Литература,
автор: nike64636
Предмет: Математика,
автор: yungvoix
Предмет: Литература,
автор: alicesmirnova9
Предмет: Математика,
автор: kfcnjxrfdjhjy